Evaluation of obesity prevalence and nutritional knowledge in adolescents in a semi urban area of Turkey - Meseri, Reci; Mermer, Gulengul; Ergin, Isil; Hassoy, Hur (Progress in Nutrition, 2015)
Objective: The objective of this study was to determine obesity prevalence and healthy nutritional knowledge among adolescents. Subjects and methods: Planned cross-sectional onset and intervention afterwards, participants were 6th&7th grade students.  Socio-demographic variables, wealth, perceived body image, nutritional habits and knowledge was questioned face to face. Weight and height was measured and evaluated via BMI percentiles. Nutritional knowledge was determined via 15 multiple choice questions. An interactive nutrition education program consisted of presentation, a game, songs and animated videos were conducted and after the intervention, nutritional knowledge was re-assessed as a post-test. Independent and dependent samples t test, logistic regression analysis, chi-square tests were conducted for analysis. p